The BNT162b2 vaccine induces humoral and cellular immune memory to SARS-CoV-2 Wuhan strain and the Omicron variant in children 5 to 11 years of age - Cinicola, Bianca Laura; Piano Mortari, E; Zicari, Anna Maria; Agrati, Chiara; Bordoni, Veronica; Albano, Christian; Fedele, Giorgio; Schiavoni, Ilaria; Leone, Pasqualina; Fiore, Stefano; Capponi, Martina; Conti, Maria Giulia; et al. (Frontiers in Immunology, 2022)
SARS-CoV-2 mRNA vaccines prevent severe COVID-19 by generating immune memory, comprising specific antibodies and memory B and T cells. Although children are at low risk of severe COVID-19, the spreading of highly transmissible variants has led to increasing in COVID-19 cases and hospitalizations also in the youngest, but vaccine coverage remains low. Immunogenicity to mRNA vaccines has not been extensively studied in children 5 to 11 years old. In particular, cellular immunity to the wild-type strain (Wuhan) and the cross-reactive response to the Omicron variant of concern has not been investigated. We assessed the humoral and cellular immune response to the SARS-CoV-2 BNT162b2 vaccine in 27 healthy children. We demonstrated that vaccination induced a potent humoral and cellular immune response in all vaccinees. By using the presence of spike-specific memory B cells as a measurable imprint of a previous infection, we found that 50% of the children had signs of a past, undiagnosed infection before vaccination. Children with pre-existent immune memory generated significantly increased levels of specific antibodies, and memory T and B cells, directed against not only the wild type virus but also the omicron variant.